Concrete: treatment of types and properties in fib Model Code 2010. (December 2013) - Müller, Harald S.; Anders, Isabel; Breiner, Raphael; Vogel, Michael
Abstract Section 5.1 "Concrete" of the fib Model Code for Concrete Structures 2010 contains basic definitions and well‐established constitutive relations for structural concrete. However, it also presents various new approaches and updated models compared with the earlier CEB‐FIP Model Code 1990. This is particularly true for the strength, stress and strain characteristics of structural concrete, for creep and shrinkage and for sophisticated durability‐related processes. The validity of the models has been extended to several types of concrete such as high strength concrete, self‐compacting concrete and lightweight aggregate concrete. The durability‐related models are either suitable for facilitating a full probabilistic service life design or for applying simpler code‐type approaches. This article provides a concise and selective overview of some of those models. Background information is summarized and there is a focus on improvements achieved by the updated models. In addition, some simple design aids are given to allow pre‐design, for example